An unusual cause of postmenopausal vaginal haemorrhage: a case report - Junyan Sun; Ying Guo; Li Ma; Zhaoxia Qian; Dongmei Lai (BMC, 2019)
Abstract Background Post-menopause vaginal haemorrhage is typically related to gynaecological malignancies. Bleeding from vaginal varices rarely occurs, especially in nonpregnant women. Moreover, nonpregnancy-related causes of vaginal varicosities include portal hypertension, especially that caused by liver cirrhosis, pelvic congestion syndrome and Klippel-Trenaunay syndrome or Parkes-Weber syndrome. Here, we report an unusual cause of nonpregnancy-associated vaginal variceal bleeding. Case presentation A 55-year-old postmenopausal woman presented in our outpatient department with complaints of recurrent bloody vaginal discharge. A group of varicose veins and several haemorrhagic spots were found on her vaginal wall during a vaginal speculum examination. Genital cancers were excluded by colposcopy and transvaginal ultrasonography; furthermore, a pelvic arteriovenous fistula was not found on a pelvic computed tomography (CT) scan. However, congenital varicosities and deep arteriovenous shunts were observed in her left leg on arterial angiography. Moreover, vaginal bleeding was improved after resolution of the underlying deep arteriovenous shunts in her left leg. Therefore, congenital arteriovenous shunts and elevated inferior vena cava pressure might be responsible for her recurrent vaginal varicose bleeding. Conclusion Haemorrhage due to vaginal varices is easily detected with a vaginal speculum examination. However, diagnosis and treatment of the original disease are important after bleeding is controlled.